The prognostic benefit of tumour-infiltrating Natural Killer cells in endometrial cancer is dependent on concurrent overexpression of Human Leucocyte Antigen-E in the tumour microenvironment. (November 2017) - Versluis, M.A.C.; Marchal, S.; Plat, A.; de Bock, G.H.; van Hall, T.; de Bruyn, M.; Hollema, H.; Nijman, H.W.
Abstract: Background: Human Leucocyte Antigen- E (HLA-E) has been reported as both a positive and negative prognostic marker in cancer. This apparent discrepancy may be due to opposing actions of HLA-E on tumour-infiltrating immune cells. Therefore, we evaluated HLA-E expression and survival in relation to the presence of intratumoural natural killer (NK) cells and cytotoxic T cells (CTLs). Methods: Tissue microarrays (TMAs) of endometrial tumours were used for immunohistochemical staining of parameters of interest. The combined impact of clinical, pathological and immune parameters on survival was analysed using log rank testing and Cox regression analyses. Results: Upregulation of HLA-E was associated with an improved disease-free and disease-specific survival in univariate analysis (HR 0.58 95% CI 0.37–0.89; HR 0.42 95% CI 0.25–0.73, respectively). In multivariate analysis, the presence of NK cells predicts survival with a hazard ratio (HR) 0.28 (95% confidence interval (CI) 0.09–0.91) when HLA-E expression is upregulated; but it is associated with a worse prognosis when HLA-E expression is normal (HR 13.43, 95% CI 1.70–106.14). By contrast, the prognostic benefit of T cells was not modulated by HLA-E expression. Conclusions: Taken together, we demonstrate that the prognostic benefit of NK cells, but not T-cells, is influenced by HLA-E expression in endometrial cancer (EC) and propose a model to explain our observations. Highlights: Upregulation of HLA-E is associated with improved survival in endometrial cancer (EC). The presence of NK cells predicts survival when HLA-E expression is upregulated. The presence of NK cells is associated with a worse prognosis when HLA-E expression is normal. The prognostic benefit of T cells is not modulated by HLA-E expression in EC. HLA-E may have opposing actions on tumour-infiltrating immune cells in EC.